2011
DOI: 10.1088/0022-3727/44/16/165405
|View full text |Cite
|
Sign up to set email alerts
|

Rapid compression preparation and characterization of oversized bulk amorphous polyether-ether-ketone

Abstract: Melts of polyether-ether-ketone (PEEK) with three kinds of average molecular weight are solidified by rapid compression from 0.1 to 2.0 GPa at 360 °C within 20 ms, and comparative samples are also made by rapid quenching and slow cooling of the same melts. Through XRD and DSC analyses and mechanical tests of the recovered samples, it is found that bulk materials of PEEK obtained by rapid compression exhibit a single amorphous phase with unique properties such as high thermodynamic stability, excellent friction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…For instance, Hong et al found that RC process could induce two amorphous phases of poly (ethylene terephthalate) (PET) which were different from that in quenched samples. Yu et al reported that the glassy sulfur obtained by RC process exhibited an exceptional thermodynamic and kinetic stability, and Yuan et al reported that the glassy polyether‐ether‐ketone samples prepared by RC exhibited high thermodynamic stability, excellent friction, and considerable stiffness in contrast to that prepared by quench cooling. In fact, it is increasingly believed that the glassy sample is in local‐ordered state with chain aggregation instead of perfectly amorphous state, and this local structure can exist while still providing a random large‐scale chain configuration .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hong et al found that RC process could induce two amorphous phases of poly (ethylene terephthalate) (PET) which were different from that in quenched samples. Yu et al reported that the glassy sulfur obtained by RC process exhibited an exceptional thermodynamic and kinetic stability, and Yuan et al reported that the glassy polyether‐ether‐ketone samples prepared by RC exhibited high thermodynamic stability, excellent friction, and considerable stiffness in contrast to that prepared by quench cooling. In fact, it is increasingly believed that the glassy sample is in local‐ordered state with chain aggregation instead of perfectly amorphous state, and this local structure can exist while still providing a random large‐scale chain configuration .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as shown in Figure A,B, a pronounced post‐ Tg endothermic peak is observed for the amorphous PLLA obtained under 200 to 400 MPa. Previous research have shown that the post‐ Tg endothermic peak could be assigned to the melting of the mesocrystal with certain chain ordering . Therefore, we speculate that the mesocrystal of PLLA could be formed during the compression process.…”
Section: Resultsmentioning
confidence: 76%
“…As mentioned above, it is found that there exists a critical formation pressure of amorphous PLLA in the crystallization process. Recently, it is reported that the amorphous materials can be obtained under pressure by the rapid compression method, and this approach is dependent on the higher pressure and the faster compression rate. Shao et al reported the preparation of amorphous PLLA by solidification under 2.0 GPa at a compression rate of 100 GPa/s.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the generation of mesophase is very likely be favored . Actually, with pressurization, the formation of metastable structures has been observed for different kinds of polymers . Therefore, pressurization can induce more effects than temperature cooling (i.e., obtaining of undercooling) on crystallization, like inducing appearance of metastable structure.…”
Section: Resultsmentioning
confidence: 99%